Polemical encounters : esoteric discourse and its others - Hammer, Olav.; Stuckrad, Kocku von, 1966- (Aries Book Series, 2007)
In its historical development from late antiquity to the present, western esotericism has repeatedly been the issue of polemical discourse. This volume engages the polemical structures that underlie both the identities within and the controversy about esoteric currents in European history. From Jewish and Christian kabbalah through heretical discourse and interconfessional polemics in early modernity to the legitimization of esoteric identity in modern culture, the 12 chapters, accompanied by an editors' introduction, provide a cornucopia of relevant cases that are interpreted in a framework of polemical discourse and 'Othering'. This volume sheds new light on the ultimately polemical structure of western esotericism and thus opens new vistas for further research into esoteric discourse.